KOMPETENSI SISWA KELAS VII 3 SMP DWI SEJAHTERA PEKANBARU DALAM MENULIS PARAGRAF DESKRIPSI TAHUN AJARAN 2014-2015: (Students’ Competence in Writing Descriptive Paragraph at Class VII 3 Dwi Sejahtera Pekanbaru Academic Year 2014-2015) - Nazirun Nazirun; Romala Sari; Karsinem Karsinem (Perspektif Pendidikan dan Keguruan, 2016)
Writing is an activity that is productive and expressive. The ability to write paragraphs areboth needed by each student. The ability to write a paragraph taught aims to make studentsable to compose or write a paragraph well so students pour their thoughts, feelings, and ideasin the work. This study aimed to describe the competence of students in writing a paragraphdescription. The study population was all students of class VII 3 totaling 29 students. Thesample was graders VII3 totaling 29 students. The hypotheses are: (1) The students’competence class VII 3 Dwi Sejahtera Pekanbaru in writing a paragraph description of theacademic year 2014-2015 in the aspect of unity categorized enough (60-74). (2) Competenceof class VII 3 Dwi Sejahtera Pekanbaru in writing a paragraph description of the academicyear 2014-2015 on cohesion aspect categorized enough (60-74). (3) Competence class VII 3junior Dwi Sejahtera Pekanbaru in writing a paragraph description of the academic year2014-2015pada aspect enough paragraph development category (60-74). This researchmethod is descriptive method. This type of research is a kind of study of Field. The researchapproach used by the authors is a quantitative research. The conclusion of this study are: (1)the students’ competence class VII 3 junior Dwi Sejahtera Pekanbaru in writing a paragraphdescription of the academic year 2014-2015 in the aspect of unity relatively less with anoverall average of 39.95 students hypothesis is rejected. (2) the students’competency at classVII 3 Dwi Sejahtera Pekanbaru in writing a paragraph description of the academic year2014-2015 on cohesion aspect classified as less with an overall average of 15.10 studentshypothesis is rejected. (3) the students’ competence class VII 3 junior Dwi SejahteraPekanbaru in writing a paragraph description of the academic year 2014-2015 ondevelopment aspects of paragraphs pertained less to the overall average of 32.6 studentshypothesis is rejected.